Fluktuasi Nilai HbA2 pada Carrier β-Thalasemia: Literature Review - Qoriba, Fathan; Sangging, Putu Ristyaning Ayu; Maulana, Muhammad; Lisiswanti, Rika (CV. Jasa Sukses Abadi, 2024)
Thalassemia is a form of microcytic anemia caused by impaired synthesis of the globin protein in hemoglobin, with β-thalassemia being one of the most common types. β-thalassemia arises from mutations in the β-globin gene located on chromosome 11, resulting in reduced or absent production of the β-globin chain. According to the World Health Organization (WHO, 2019), the global prevalence of β-thalassemia major is estimated at 39.96 million people (5.2% of the world’s population), with 1.5% identified as carriers. In Indonesia, the 2018 Riskesdas survey reported 7,209 cases of β-thalassemia. The decreased synthesis of the β-globin chain leads to elevated levels of HbA2 and HbF. β-thalassemia is classified into three categories: minor, intermediate, and major. This review focuses on the characteristics of HbA2 and its significance in diagnosing the β-thalassemia carrier. This article is a narrative literature review that examines various studies on HbA2 (HbA2) and its role in the β-thalassemia carrier. The literature reviewed was sourced from several databases, including PubMed, Google Scholar, and Elsevier, using the keywords